Indonesia - Mahdiyah Mumtaz, Difa; Wiguna, Didik; Katarina, Dona (PROFITABILITAS, 2023)
This study aims to create a computerized goods sales system and produce a program that can reduce errors in managing goods sales data, as well as make work more efficient and effective at the previous Deliberation Shop. Creating storage media that is safer than paper, making reports easier and more accurate, and creating displays that can assist in the process of inputting and calculating transactions. The research method used in this study is the FIFO (First In First Out) method, namely by collecting data through observation, interviews and literature study. Where in making the design of this application design tools such as the Unfield Modeling Language (UML) are used in which there are Use Case Diagrams, Sequence Diagrams, Class Diagrams, and also ERD (Entity Relationship Diagram), and use the Java programming language with the Netbeans editor and MySQL Database using XAMPP. The result of this study is that there is an application for selling goods that can help the process of selling goods and also makes it easy for Deliberation Stores to manage customer data, goods data and sales transaction data stored in the database.